(untitled) (Educational Dimension, 2020)
The article is devoted to the formation of digital competence of pedagogical university students. The scientific analysis of the essence of the “digital competence” concept is carried out, its components are defined. In the course of the research the components of digital competence of pedagogical university students are determined, namely: motivational-value (target), cognitive, operational-activity and personal-reflexive components. The article defines and substantiates didactic conditions of digital formation competences of students of pedagogical universities: actualization of motivational value training of students of pedagogical universities; organization of interaction between students and teachers of pedagogical universities on the Internet through the creation of digital information educational environment; creation of individual educational trajectories of students.